Changing paatterns of gender portrayals in portuguese television advertisements - Felix Neto (2009)
The purpose of this study was to identify patterns in Portuguese television advertisements and interpret changes in the portrayal of gender roles using data collected 7 years apart: 1996 and 2003. We grouped 11 attributes of the central figure displayed in 623 evening commercials using a k-means cluster procedure. There were 4 distinct groups of advertisements that emerged, 2 of them characterizing a predominantly male central figure and the other 2 a female central figure. The overall increase in women portrayed in advertisements from 1996 (32.9%) to 2003 (40.8%) is reflected in a shift toward an increase of advertisements with a female central figure in the typically male "narrator" cluster. Practical implications of these findings are discussed.